The Norton Sampler : (W. W. Norton, 1982)
As a rhetorically arranged collection of short essays for composition, the Sampler echoes the cloth samplers once done in colonial America, presenting the basic patterns of writing for students to practice just as schoolchildren once practiced their stitches and ABCs on needlework samplers. This new edition shows students that description, narration, and the other patterns of exposition are not just abstract concepts used in composition classrooms but are in fact the way we think—and write. The Norton Sampler contains 63 carefully chosen readings—classics as well as more recent pieces, essays along with a few real-world texts—all demonstrating how writers use the modes of discourse for many varied purposes